A patient-specific lower extremity biomechanical analysis of a knee orthotic during a deep squat movement. (June 2020) - Christine, Walck; Victor, Huayamave; Daryl, Osbahr; Todd, Furman; Tyler, Farnese
Highlights: Knee joint orthosis improves the activation in the subject's posterior chain musculature. Non-linear spring-loaded knee joint orthosis encourages a more neutral behavior by inhibiting movement towards terminal knee extension. Non-linear spring-loaded knee joint orthosis may have a performance influence by targeting posterior chain activation. Non-linear spring-loaded knee joint orthosis reduce rectus femoris and soleus force generation. NLSL KJO encourages a more balanced synergy versus the inherent quadriceps dominant strategy during the squat movement. Abstract: Although knee orthotics have become the preferred treatment method for rehabilitation and injury prevention, their biomechanical influence has not yet been quantified. A new type of knee joint orthosis (KJO) using a non-linear spring-loaded (NLSL) component was recently introduced to help prevent the growing number of knee injuries and aid during rehabilitation. The purpose of this case study is to quantify the lower extremity biomechanical effects and evaluate functional benefits of a new KJO as a precision treatment option. Kinematic and kinetic data obtained from two dynamic squat trials were recorded using VICON Ⓡ motion capture system and an AMTI Ⓡ force plate. This data was then applied to a modified computational musculoskeletal model. Inverse kinematics and dynamics were performed to calculate joint angles and joint moments while a static equilibrium problem was solved at each instant during the squat cycle, with and without the NLSL KJO to find individual muscle forces of the lower extremity. The NLSL KJO was seen to improve the activation in the subject's posterior chain musculature encouraging a more balanced synergy versus the inherent quadriceps dominant strategy during the squat movement, and encourage a more neutral behavior in the upright position by inhibiting movement towards terminal knee extension.